Arabidopsis formin 2 regulates cell-to-cell trafficking by capping and stabilizing actin filaments at plasmodesmata - Diao, Min; Ren, Sulin; Wang, Qiannan; Qian, Lichao; Shen, Jiangfeng; Liu, Yule; Huang, Shanjin (eLife, 2018)
Here, we demonstrate that Arabidopsis thaliana Formin 2 (AtFH2) localizes to plasmodesmata (PD) through its transmembrane domain and is required for normal intercellular trafficking. Although loss-of-function atfh2 mutants have no overt developmental defect, PD’s permeability and sensitivity to virus infection are increased in atfh2 plants. Interestingly, AtFH2 functions in a partially redundant manner with its closest homolog AtFH1, which also contains a PD localization signal. Strikingly, targeting of Class I formins to PD was also confirmed in rice, suggesting that the involvement of Class I formins in regulating actin dynamics at PD may be evolutionarily conserved in plants. In vitro biochemical analysis showed that AtFH2 fails to nucleate actin assembly but caps and stabilizes actin filaments. We also demonstrate that the interaction between AtFH2 and actin filaments is crucial for its function in vivo. These data allow us to propose that AtFH2 regulates PD's permeability by anchoring actin filaments to PD.
Keywords: plasmodesmata; actin; formin; intercellular trafficking; size exclusion limit of PD; cucumber mosaic virus